Impact of Green Finance on Environmental Performance with the Mediation of Financial Innovation: Evidence from Nigerian Bank - Adeyemi, Adewumi Z.; Olasupo, Sunday F.; Johnson, Adebayo A.; Adegun, Emmanuel A.; Sajuyigbe, Ademola S. (Universitas Airlangga, 2024)
Objective: This study examines the mediating effect of financial innovation on the relationship between green finance and environmental performance. Design/Methods/Approach: A targeted sampling technique was used for access bank selection. Copies of the structured questionnaire were sent to 250 branch managers of Access Bank in southwestern Nigeria. A total of 200 questionnaires were completed and returned to researchers. Data were analyzed using the STATA 15 version using structural equation modeling. Findings: The results show that green loans, green training, green investment, and green policy have a positive and significant impact on environmental performance. This means that green finance parameters are the driving force behind Nigeria's environmental initiatives and performance. Furthermore, the study showcases that financial innovation partially mediates green loans, green investments, green training, and environmental performance. The study also confirms that financial innovation does mediate green policy and environmental performance. Originality/Value: Prior studies have confirmed the correlation between green finance and environmental outcomes. However, despite various research endeavors highlighting the influence of green finance on overall ecological performance and introducing financial innovation as a mediator, this aspect remains unexplored in the context of the banking sector. Practical/Policy implication: Given that financial innovation partially mediates green loans, green investments, green training, and environmental performance, the results of this investigation are of importance to policymakers and financial institutions in the area of banks' environmental performance. This study provides insights on financial innovation and green finance in financial institutions to foster green banking activities to promote environmental sustainability and performance.